The development of admissions policy in Saudi universities to achieve competitiveness in the light of global experiences. - Al-Qarni, Hawaa bint Muhammad bin Ali (Journal of Educational and Psychological Sciences, 2018)
The study aimed to present a vision for the development of admissions policy in Saudi universities to achieve competitiveness in the light of international experiences. The researcher used the Survey and documentary descriptive approach and a questionnaire of 37 words distributed on two main axes that were distributed to all the study population who are deans, deputies, officials and decision makers in (28) public universities, (50) individuals responded. And by analyzing the statistical program (SPSS), the researcher reached several results, the most important of which are: 1 - The reality of admissions policy in Saudi universities on average (2.33) high degree. 2- The needed requirements for developing the admissions policy in the Saudi universities to achieve competitive capabilities in the light of international experiences have reached a high average of (2.44). 3- The researcher presented a proposed conception for the development of admission policy in Saudi universities to achieve competitive capabilities in the light of international experiences. It also recommended reconsidering the policy of admission and linking it to development plans and the needs of society.